Sustainable and Enhanced Production of Glucose Oxidase by Aspergillus niger Using Pineapple Rind as an Economical Substrate for Biomedical and Biosensor Applications - Gadiparthi, Harika; Simhadri, Hema Gayatri; Chanda, Chandrasekhar (International Journal of Pharmaceutical Investigation, 2026)
Objectives Glucose Oxidase (GOx) is a essential enzyme used in several industries, including food, pharmaceuticals, and biotechnology. However, commercial-scale production continues to face challenges due to high processing costs and the environmental impact linked with conventional manufacturing approaches. Materials and Methods In this work, a simple and sustainable method was explored to enhance GOx production using Aspergillus niger cultivated on pineapple rind. Results The findings indicated that pineapple rind served as an excellent fermentation substrate, producing a noticeably higher enzyme yield compared to routinely used media. These results highlight the potential of agricultural waste materials such as pineapple rind as an efficient, low-cost option for large-scale GOx production. Utilizing this agro-industrial residue not only lowers production expenses but also offers an eco-friendly solution by converting waste biomass into a useful resource. Conclusion The study establishes the feasibility of achieving enhanced GOx production, reaching up to 136 IU/mL, thereby highlighting a greener and more economical approach for industrial enzyme manufacture.
Keywords: Aspergillus niger; Glucose Oxidase enzyme; Pineapple rind; Sustainable production